(3GdNUNUI hJCKjQGJgG GdGbJUGOjI (B/s - (3CHh YGeQjI, aGdMs ((3YeGf(B: s (3OGQ GSGeI ddfTQ h GdJhRjY(B, s, 2007)
(3GdeMJhjGJ (B: (3GdebOeI(B-(3GdaUd GdGhd (B: (3GdNUNUI (B: (3acQI GdNUNUI (B: (3JUGYO GdEJLGg UhH GdNUNUI(B-(3GdaUd GdKGfj (B: (3GdNUNUI hab QDjI ESdGejI (B: (3GgOGa GdNUNUI(B-(3GdaUd GdKGdK (B: (3eJWdHGJ SjGSGJ GdNUNUI hJCKjQGJgG GdeNJdaI (B: (3cjajI JWHjb GdNUNUI(B-(3GdaUd GdQGHY (B: (3CSGdjH GdNUNUI hSHd GdGSJaGOI efgG (B: (3GSGdjH YedjI GdNUNUI(B-(3GdaUd GdNGeS (B: (3GdGSJKeGQ GdCLfHj hGdNUNUI(B-(3GdaUd GdSGOS (B: (3GdMce GdQTjO hNUNUI GdeDSSGJ (B: (3CgejI GdMce GdQTjO(B-(3GdaUd GdSGHY (B: (3JQhjL bVGjG GdNUNUI (B: (3CgejI GdJQhjL dbVGjG GdNUNUI aj GdOhd GdfGejI(B-(3GdaUd GdKGef (B: (3WQb GdNUNUI (B: (3QDjI JShjbjI aj Cge bVGjG GdNUNUI(B-(3GdaUd GdJGSY (B: (3GdNUNUI hBKGQgG GdGbJUGOjI GdeJhbYI Ydi GdGbJUGOjGJ GdYQHjI(B-(3GdaUd GdYGTQ (B: (3SjGSGJ GdJNUjU OQGSI dJLQHI OhdI bWQ (B: (3eaghe GdJNUjU(B-(3GdaUd GdMGOj YTQ (B: (3GdNUNUI aj GdeedcI GdYQHjI GdSYhOjI deGPG CHWC EjbGYgG (B: (3VQhQI GdJegjO (B: (3GdHYV dG jQjO(B-(3GdaUd GdKGfj YTQ (B: (3UfOhb GdfbO GdOhdj hNUNUI GdGbJUGO GdYQGbj (B: (3GdEeHQGdjI GdGbJUGOjI ddhdGjGJ GdeJMOI(B-(3GdaUd GdKGdK YTQ (B: (3GdNUNUI aj eUQ (B: (3YedjI NUNUI GdHfc GdeUQj GdCeQjcj(B-(3GdaUd GdQGHY YTQ (B: (3NUNUI aj dHfGf (B: (3GdNUNUI aj dHfGf gd gj NjGQ GdeQMdI, hSeI GdYUQ(B.s
Keywords: (3GdbWGY GdNGUs; (3GdbWGY GdNGU(B- (3eUQ s; (3LhGfH GbJUGOjIs